Comparison of interrupted and continuous modulator therapy in cystic fibrosis: a real life experience in Turkey - Ergenekon, Almala Pinar; Selcuk, Merve; Unal, Gokcen; Gozen Bayramoğlu, Gamzegul; Altuntas, Cansu; Kose, Mehmet; Basaran, Abdurrahman Erdem; Can Oksay, Sinem; Uytun, Salih; Oktem, Sedat; Uyan, Zeynep Seda; Canitez, Yakup; et al. (Frontiers in Pediatrics, 2025)
IntroductionCystic fibrosis (CF) transmembrane conductance regulator protein (CFTR) modulators have significantly improved health outcomes in patients with cystic fibrosis (pwCF). However, in Turkey, access is limited due to lack of insurance coverage, and treatment is only granted in 3-month periods via court rulings. This study aimed to compare clinical outcomes between patients receiving continuous vs. intermittent modulator therapy.MethodsIn this retrospective multicenter study, data from 229 CF patients across 14 centers in Turkey who received highly effective modulator therapy (HEMT) for at least six months were analyzed. Patients were grouped based on whether they received treatment continuously (Group 1) or with interruptions (Group 2). Changes in percent predicted forced expiratory volume in one second (ppFEV₁) and body mass index (BMI) were evaluated at baseline, 3 months, and 6 months. For Group 2, ppFEV₁ was also assessed during interruption periods.ResultsOf the 229 patients, 38.4% received continuous treatment while 61.5% experienced treatment interruptions. Both groups showed significant improvements in ppFEV₁ over six months (p < 0.001). However, Group 2 experienced a significant decline during interruption periods (p < 0.001), followed by recovery upon reinitiation. BMI also increased significantly in both groups (p < 0.05). Patients with baseline ppFEV₁ < 70% showed greater improvement compared to those with milder disease.ConclusionShort-term clinical outcomes in ppFEV₁ and BMI were similar between continuous and intermittent treatment. However, treatment interruptions may reduce cumulative benefits, potentially impacting long-term outcomes. Ensuring uninterrupted access to HEMT is essential, especially in low- and middle-income countries.